PERBEDAAN TATA BUSANA DAN TATA RIAS ANTARA PERTUNJUKAN KETOPRAK DAN KABUKI - Nur Hastuti (IZUMI, 2013)
Abstract Kabuki and ketoprak are two art performances that are still growing and liked by their supportive society. Some elements of kabuki and ketoptrak making us easy to recognize what performance is being played, beside the actors and actresses get dressed and make up. The actors and actresses of kabuki and ketoprak must know how to get dressed and make up. Things the actors and actresses should consider in making up the face are the face, characters, and the actors face shape. While the actors and actresses of kabuki wear kimono. Keywords: dress, make up, characters, face shape, kimono